Full house Keren Cytter - Wesseler, Moritz 1980- (Verlag der Buchhandlung Walther und Franz König, 2022)
The artist’s book Full House is based on a new series of drawings by Keren Cytter, who was born in 1977 in Tel Aviv. The images depict the interior of apartments in Netanya, Lausanne, and New York, in which the artist and writer lived between 2020 and 2022. Cytter used a variety of felt-tips to make the drawings, which are composed like puzzles, but here the pieces do not seem to quite fit together. In this way, the view into the everyday life of Cytter, which is not least reminiscent of the tradition of diaries, is regularly undermined. [publisher’s information]
Auflage/edition: 500
Keywords: Tsịter, Ḳeren -- 1977-; Zeichnung; Keren Cytter; Moritz Wesseler; Zeitgenössische Kunst; Bildende Kunst; Friedericianum, Kassel; Bildband; Künstlerbuch